Plant you : 140+ ridiculously easy, amazingly delicious plant-based oil-free recipes - Bodrug, Carleigh (Hachette Go, an imprint of Hachette Books, 2022)
"Tacos, pizza, wings, pasta, hearty soups, and crave-worthy greens-for some folks looking for a healthier way of eating, these dishes might all seem, well, off the table. Carleigh Bodrug has shown hundreds of thousands of people that that just isn't true. Like so many of us, Carleigh thought that eating healthy meant preparing the same chicken breast and broccoli dinner every night. Her skin and belly never felt great, but she thought she was eating well--until a family health scare forced her to take a hard look at her diet and start cooking and sharing recipes. Fast forward, and her @plantyou brand continues to grow and grow, reaching +470k followers in just a few short years. Her secret? Easy, accessible recipes that don't require any special ingredients, tools, or know-how; what really makes her recipes stand out are the helpful infographics that accompany them, which made it easy for readers to measure ingredients, determine portion size, and become comfortable enough to personalize recipes to their tastes. Now in her debut cookbook, Carleigh redefines what it means to enjoy a plant-based lifestyle with delicious, everyday recipes that anyone can make and enjoy. With mouthwatering dishes like Bewitchin' Breakfast Cookies, Rainbow Summer Rolls, Irish Stew, and Tahini Chocolate Chip Cookies, this cookbook fits all tastes and budgets. PlantYou is perfect for beginner cooks, those wishing to experiment with a plant-based lifestyle, and the legions of "flexitarians" who just want to be healthy and enjoy their meals"--